Hubungan Pemeriksaan Triple Eliminasi terhadap Pencegahan Penyakit Menular Seksual pada Ibu Hamil - kolifah kolifah; Dwi Srirahandayani; Erika Agung Mulyaningsih; Mudhawaroh (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
The risk of vertical transmission of HIV/AIDS, Hepatitis B, and Syphilis from mother to child is significant. The likelihood of HIV/AIDS being transmitted vertically from mother to kid varies between 20% and 45%, for syphilis it ranges from 69% to 80%, and for Hepatitis B it surpasses 90%. Every expectant mother has triple screening for HIV, Syphilis, and Hepatitis B to reduce the risk of transmission to the newborn. As to the Ministry of Health of the Republic of Indonesia (2019), it is obligatory for pregnant women to undergo triple elimination screening to mitigate the transmission of HIV/AIDS, Syphilis, and Hepatitis B. The research aimed to evaluate the effectiveness of the Triple Elimination Examination in preventing the spread of sexually transmitted illnesses among pregnant women in Mojongapit Village, Jombang. This study is a retrospective cohort investigation that specifically examines mothers who had their babies in Mojongapit Village. Carry out study from June to August 2023. The study's independent variable is the triple elimination examination, whereas the dependent variable is the incidence of diseases transmitted from mother to newborn. A purposeful selection method was used to choose twenty-eight mothers who had previously given birth, and their history of triple elimination examination was observed. Performing analysis using the Spearman rank correlation approach. The research revealed that 96.2% of the 25 mothers who were not infected with sexually transmitted illnesses had triple elimination examinations in the first trimester. The Spearman Rank statistical test resulted in a p value of 0.000, demonstrating a strong correlation between the occurrence of sexually transmitted infections and the implementation of triple elimination examinations in Mojongapit Village, Jombang. The implementation of the triple elimination initiative, which includes screening, treatment, and is characterized by its cost-effectiveness and efficiency, has shown its effectiveness in avoiding the transmission of HIV, syphilis, and hepatitis B from mother to child.